Flexibilidade metabólica em resposta ao treinamento de força e terapia de fotobiomodulação em idosas sedentárias - Moura, Ronaldo Ferreira (2025)
Background: Metabolic flexibility refers to an organism's ability to switch between energy substrates in response to different conditions and stimuli, such as circadian variation, sleep, fasting, feeding, conservation, and exercise, usually appropriate to substrate availability and energy demand. Studies show that various chronic diseases and advanced age are strongly related to metabolic inflexibility, and that physical exercise can improve it. Impaired metabolic flexibility is directly related to aging and appears to be more frequently present in older adults due to post-menopausal metabolic and hormonal changes. However, there are several methods that can be used to improve metabolic flexibility, such as photobiomodulation therapy (PBMT), including in combination with physical exercise. Objective: To evaluate the metabolic flexibility of sedentary older adults in response to resistance training (RT) combined with PBMT or RT alone. Methods: Nineteen elderly women were allocated into two groups, RT (n = 9, 68.44 ± 5.27 years) and RT plus PBMT (RTPT) (n = 10, 69.40 ± 5.21 years). The RTPT group received PBMT, while for the RT group, the equipment was turned off (sham). Body composition was assessed by DXA (Dual Energy X-ray Absorptiometry). For the RT protocol to be used with linear periodization, no intensity was increased every two weeks, starting with 10 repetitions at 70% of 10RM in the first weeks and ending with 10 repetitions at 100% of 10RM in the last weeks.The protocol consisted of three weekly sessions, with an average duration of 50 minutes per session, for a total of 24 sessions. An incremental treadmill test was performed before and after the 24 sessions. The test began with an initial speed of 3 km/h and a 3% setting, with an expected final speed of 6 km/h and a 12% setting. After the start, the speed and extension gradually increased: 0.1 km/h every 10 seconds and 0.5% every 40 seconds, respectively. along with the test, a gas analysis was performed to record the variables of heart rate (HR), oxygen consumption (VO2), carbon dioxide production (VCO2), and power (PO) in three aspects: anaerobic threshold (AT), respiratory compensation point (RCP), and maximum oxygen consumption (VO2max), and thus verify the results of metabolic flexibility. Results: Compared to pre-intervention values, the RTPT group showed significant differences in VO2max (pre: 18.32 ± 3.01; post: 21.89 ± 2.35 mL/kg/min), carbohydrate oxidation (CHox) (pre: 1.54 ± 0.61; post: 2.45 ± 0.91 g/min), CHox/fat-free mass (pre: 36.12 ± 12.28; post: 55.92 ± 16.74 mg/min/kg FFM), and energy expenditure (EE) normalized to FFM, EE/FFM (pre: 147.00 ± 49.95; post: 227.56 ± 68.08 kcal/min/FFM) during the incremental maximal effort test, while the RT group: VO2max (pre: 18.98 ± 5.03; post: 21.16 ± 4.88 mL/kg/min), CHox (pre: 1.42 ± 0.69; post: 1.91 ± 0.52 g/min), CHox/FFM (pre: 36.07 ± 16.93; post: 46.51 ± 11.10 mg/min/kg FFM) and EE/FFM (pre: 146.79 ± 68.79; post: 189.26 ± 45.16 Cal/minFFM) did not show a significant difference. However, with regard to power output (PO), both groups showed similar increases, 135.66 ± 38.54 W pre-intervention and 151.47 ± 59.90 W post intervention for RT and 170.46 ± 45.49 W pre-intervention and 193.30 ± 46.90 W post intervention for RTPT. Conclusion: The intervention with RT combined with PBMT results in a positive impact on the metabolic variables of sedentary elderly individuals when 7 compared to RT alone, making this approach a viable alternative to improve metabolic variables during an incremental trial.